Gefitinib: re-emerging from the shadows. (October 2013) - Martin, Petra; Owen, Scott P; Leighl, Natasha B
SUMMARY  In the past decade, the identification of mutations in the EGFR gene and the sensitivity of activating mutations to EGF receptor–tyrosine kinase inhibitors has improved survival in a subset of non-small-cell lung cancer patients. Over 70% of patients with EGFR mutations have a response to gefitinib therapy. Gefitinib, a first-generation EGF receptor–tyrosine kinase inhibitor, is well tolerated and continues to be widely used. However, eventually most patients develop resistance to gefitinib. This article reviews the pharmacology of gefitinib and summarizes the clinical trials that have resulted in its current day indications.